UNVEILING THE COMMUNICATION SKILLS DYNAMICS OF INDONESIAN STUDENTS IN INTERNATIONAL CREDIT TRANSFER PROGRAM: A PHENOMENOLOGICAL INQUIRY INTO ACADEMIC LIVED EXPERIENCES IN THE PHILIPPINES - Febiola, Febiola; Maulina, Maulina; Nasrullah, Rahmat (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to explore the dynamics of communication skills of Indonesian students’ lived experiences during the International Credit Transfer (ICT) program in the Philippines. We apply the phenomenology method with a stimulated-recall interview to find out students' lived experiences to recall the communication skill dynamics while studying at Nueva Ecija University of Science and Technology in the Philippines for one semester. 3 students (1 female and 2 male students) as participants were selected purposively. Data was analyzed thematically following six phases, 1) become familiar with the data, 2) generate initial codes, 3) search for themes, 4) review themes, 5) define themes, and 6) write-up. The result of the research demonstrated that after taking part in the ICT program, Indonesian students' communication abilities increased in three areas: verbal, written, and social communication skills. Verbal communication skills involve idea presentation, overcoming language barriers, collaborative presentation, and teamwork. While written communication skills include aspects of using social media for collaboration, assignment models, and active communication involvement. Besides, social communication skills include reaching a consensus, body language communication, cultural sensitivity, and language learning. All these information provides a significant communication skills impact enhancement that offers Indonesian students a valuable opportunity to enhance their communication skills verbally, written, and social through various classroom activities and interactions in the ICT program.